Phylogenetic relationships between Prorocentrum and Dinophysis, two potential Diarrhetic Shellfish Poison (DSP) producing Dinoflagellates, based on Ultrastructure and Mitochondrial B (Frg0101-NSNH-1/2007) - Normawaty Mohammad Noor; Ann Anton; Ojvind Moestrup (Universiti Malaysia Sabah, 2007)
This study was carried out to investigate the morphological relationship between Prorocentrum and Dinophysis, and to identify other characteristics (morphology and new gene-cytochrome b) to improve the classification of Prorocentrum. To achieve these objectives ultrastructural study (SEM and TEM) were carried out on D. acuminata and P. hoffmaniannum. Results showed that Dinophysis has 4 platelets surrounding the flagellar pore as has been suggested in study elsewhere. Prorocentrum hoffmaniannum has 8 platelets in the periflagellar area and SEM is not suitable to determine the number of platelets for Prorocentrum species. The relationship between these two genera based on platelets configuration cannot be resolved until more Dinophysis species have been studied. Prior to molecular analysis, the morphology characteristics of six Prorocentrum species were identified using light and SEM. The morphological characteristic of these Prorocentrum species agreed well with previous descriptions. Prorocentrum norrisianum identified in this study is similar morphologically to P. cassubicum. Phylogenetic study based on cytochrome b on 9 species of Prorocentrum and 14 other dinoflagellates showed that Prorocentroids is monophyletic as suggested morphologically. The Prorocentroid can be divided into 4 groups based on combination morphological characteristics and toxin production. Ecology study showed that Prorocentrum preferred seagrasses rather than seaweed and sand.